The The Impact of Reinvention Reforms and Public Service Motivation on Organizational Performance in Government Agencies: The Impact of Reinvention Reforms and Public Service Motivation on Organizational Performance - Liu, Hsiang-Te; Chao, Ren-Fang; Wu, Tsung-Lin; Hsu, Li-Yi (Advances in Social Sciences Research Journal, 2021)
The pursuit of organisational performance has long been a focus of administrative innovation in government agencies. To understand the impact of reinvention reforms and public service motivation on organisational performance in the public sector, the present study conducted a survey with civil servants in Taiwan as the research subjects. A total of 953 valid questionnaires were collected and analysed using structural equation modelling. The results show that reinvention reforms have a significant positive impact on public service motivation, and that public service motivation has a significant positive effect on both internal organisational performance and external organisational performance. In addition, the present study also confirms that public service motivation plays a mediating role between reinvention reforms and internal organisational performance and external organisational performance.